The multifaceted effects of polysaccharides isolated from Dendrobium huoshanense on immune functions with the induction of interleukin-1 receptor antagonist (IL-1ra) in monocytes. - Juway Lin; Ya-Jen Chang; Wen-Bin Yang; Alice L Yu; Chi-Huey Wong (PLoS ONE)
Dendrobium huoshanense is a valuable and versatile Chinese herbal medicine with the anecdotal claims of cancer prevention and anti-inflammation. However, its immunological activities are limited to in vitro studies on a few cytokines and immune cell functions. First, we investigated the effects of polysaccharides isolated from DH (DH-PS) on inducing a panel of cytokines/chemokines in mice in vivo and human in vitro. We found that DH polysaccharides (DH-PS) induced TH1, TH2, inflammatory cytokines and chemokines in mouse in vivo and human cells in vitro. Secondly, we demonstrated that DH-PS expanded mouse splenocytes in vivo including CD4(+) T cells, CD8(+) T cells, B cells, NK cells, NKT cells, monocytes/macrophages, granulocytes and regulatory T cells. Notably, DH-PS induced an anti-inflammatory molecule, IL-1ra, in mouse and human immune cells, especially monocytes. The serum level of IL-1ra elicited by the injection of DH-PS was over 10 folds of IL-1β, suggesting that DH-PS-induced anti-inflammatory activities might over-ride the inflammatory ones mediated by IL-1β. The signaling pathways of DH-PS-induced IL-1ra production was shown to involve ERK/ELK, p38 MAPK, PI3K and NFκB. Finally, we observed that IL-1ra level induced by DH-PS was significantly higher than that by F3, a polysaccharide extract isolated from another popular Chinese herbal medicine, Ganoderma lucidum. These results indicated that DH-PS might have potential applications for ameliorating IL-1-induced pathogenic conditions.